Seed : A Novel - Crawford, Stanley G., 1937- (Book collections on Project MUSE., 2014)
Seed is the story of Bill Starr's final days. Childless but with a lifetime's worth of possessions and a nearly infinite web of extended family, Bill endeavors to empty his house completely before he dies by summoning distant relatives to claim their inheritance. Many of his letters go unanswered, but those who do appear show up only to find that their reward is often much less valuable than they might expect. What they get instead are Bill's memories, made vivid by each item from the past, memories that are more exotic and curious than the lives currently lived by his young relatives. Accompa.